Prevalence, Risk Factors, and Clinical Correlates of Insomnia in China College Student During the COVID-19 - Yu, Chang; Li, Xingxing; Qi, Gangqiao; Yang, Liang; Fu, Wenbo; Yao, Qin; Wei, Lei; Zhou, Dongsheng; Zhang, Xiangyang; Zheng, Hong (Frontiers in Psychiatry, 2021)
Abstract: Objective: The 2019 novel coronavirus disease (COVID-19) broke out in Hubei Province and spread rapidly to the whole country, causing huge public health problems. College students are a special group, and there is no survey on insomnia among college students. The purpose of this study was to investigate the incidence and related factors of insomnia in college students during the period of COVID-19. Method: A total of 1086 college students conducted a cross-sectional study through the questionnaire star platform. The survey time was from February 15 to February 22, 2020. The collected information included demographic informatics and mental health scale, Athens Insomnia Scale (AIS) to assess sleep quality, Self-Reporting Questionnaire-20 (SRQ-20) to assess general psychological symptoms, Chinese perceived stress scale (CPSS) to assess stress. We used logistic regression to analyze the correlation between related factors and insomnia symptoms. Results: The prevalence of insomnia, general psychological symptoms and stress were 16.67 %,5.8 %and 40.70 %, respectively. Multivariate logistic regression analysis showed that gender (OR=1.55, p=0.044, 95% CI=1.00–2.41), general psychological symptoms (OR=1.49, p < 0.01, 95% CI=1.40–1.60) and living in an isolation unit (OR=2.21, p =0.014, 95% CI=1.17–4.16) were risk factors for insomnia of college students. Conclusion: Our results show that the insomnia is very common among college students during the outbreak of covid-19, and the related factors include gender, general psychological symptoms and isolation environment. It is necessary to intervene the insomnia of college students and warrants attention for mental well-being of college students.